المعاقبة على انتهاكات القانون الدولي الإنساني في التشريعات الوطنية - إشوي عماد; منار فاطمة الزهرة; منار صبرينة (مجلّة الباحث في العلوم القانونية والسياسية, 2020)
In order to suppress violations of international humanitarian law, there must be criminal laws which define such crimes against innocent people, and the perpetrators penalties. This paper discusses the punishments provided for violations of this branch of law in national legislation, through the relationship between international law and national law, then The legal basis for the obligation to do so is addressed, as provided for in legal texts, with various means of double criminalization, differentiating between the public and private criminalization, in addition to the obligation of punish Grave Breaches of this law also. whereas models of certain European laws application, which have taken real measures to fulfill their commitment to punish international humanitarian law violations, then we discuss in this research the attempts of Arab countries in the same regard.
Keywords: Punishment; Grave Breaches; International Humanitarian Law; National Criminal Law